Methodology to Optimize Manufacturing Time for a CNC Using a High Performance Implementation of ACO - Montiel-Ross, Oscar; Medina-Rodríguez, Nataly; Sepúlveda, Roberto; Melin, Patricia (International journal of advanced robotic systems, 2012)
In this paper, an efficient methodology to generate optimal and/or quasi-optimal sequences of G commands to minimize the manufacturing time is presented. Our solution starts from original G codes provided by application CAD/CAM software. Here, first we tackled the problem of reducing the time of the travel path for drilling of an industrial robotic manufacturing machine. The methodology can be easily implemented for free distribution or commercial CAD/CAM software without achieving any modification to it. Several experiments that demonstrate how this proposal can help to outperform solutions provided by application software are presented, consistent improvements around 62% were obtained. Moreover, for optimizing the time along the travel path, we present a high performance implementation of Ant Colonies (ACO) known as Parallel ACO (P-ACO) that allows achieving the optimization task efficiently by speeding up the original ACO. A Graphical User Interface that integrates the whole process is shown.